Causal inference methods to study gastric tube use in amyotrophic lateral sclerosis. (3rd October 2017) - McDonnell, Erin; Schoenfeld, David; Paganoni, Sabrina; Atassi, Nazem
Abstract : Objective: To estimate effects of gastric tube (G-tube) on survival and quality of life (QOL) in people with amyotrophic lateral sclerosis (ALS) correcting for confounding by indication inherent in nonrandomized observational data. Methods: To complement a recent causal inference analysis, which concluded that G-tube placement increases the hazard of death, permanent assisted ventilation, or tracheostomy by 28%, we fit causal inference models on a different sample of 481 patients with ALS enrolled in a recent clinical trial of ceftriaxone. Forward selection identified predictors of G-tube placement. Effects of G-tube on survival and QOL were estimated using structural nested models and marginal structural models, accounting for predictors of G-tube treatment. Results: Forced vital capacity and the total score and bulbar subscale of the revised ALS Functional Rating Scale best predicted G-tube placement. Correcting for these confounders, G-tube placement decreased survival time by 46% ( p < 0.001) and had no effect on QOL ( p = 0.078). Sensitivity survival analyses varied in significance, but none revealed a survival benefit. Conclusions: In the absence of randomization, causal inference methods are necessary to correct for time-varying confounding. G-tube placement may have a negative effect on survival with no QOL-related benefit for people with ALS. A randomized controlled trial is warranted to further evaluate the efficacy of this widely used intervention. Clinicaltrials.gov identifier: NCT00349622. Classification of evidence: This study provides Class III evidence that for patients with ALS, G-tube placement decreases survival time and does not affect QOL.